Addictions - Teesson, Maree (Hove, East Sussex : Psychology Press, 2012)
'The first edition of Addictions established itself as a valuable resource for students and professionals alike. This authoritative new edition builds on the success of the previous book, incorporating advances in research and practice over the last ten years. The book includes material on: - the nature of addiction and who becomes addicted - health consequences of alcohol and other drug dependence - theories and causes of addition. The authors, experts in the field, also include new material on the controversy surrounding the possible positive effects of alcohol and cannabis use, the increased risk of interpersonal violence, and new research on theories of addiction. Addictions will be essential reading for students, professionals and researchers seeking state of the art information about this rapidly growing field'--
Prev. ed. ented under Teesson, Maree.
Includes bibliographical references (p. 119-144) and index.
Keywords: Substance abuse -- Treatment; Substance abuse -- psychological aspects; Addicts